2007
DOI: 10.4049/jimmunol.179.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: T Cells Respond to Lipopolysaccharide Innately via TLR4 Signaling

Abstract: LPS, a molecule produced by Gram-negative bacteria, is known to activate both innate immune cells such as macrophages and adaptive immune B cells via TLR4 signaling. Although TLR4 is also expressed on T cells, LPS was observed not to affect T cell proliferation or cytokine secretion. We now report, however, that LPS can induce human T cells to adhere to fibronectin via TLR4 signaling. This response to LPS was confirmed in mouse T cells; functional TLR4 and MyD88 were required, but T cells from TLR2 knockout mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 28 publications
3
77
1
Order By: Relevance
“…We found that LPS could costimulate T cells to make IFN-␥ in the presence of IL-2 to the same on May 10, 2018 by guest http://iai.asm.org/ extent as bacterial infection in both CD4 ϩ and CD8 ϩ T cells. TLR4 expression on memory T cells has been reported (4) and, although stimulation via LPS alone does not result in proliferation nor cytokine production, T cells are able to respond to LPS via TLR4 by upregulating adherence to fibronectin and SOCS3 (39). Thus, LPS may be able to directly costimulate human T cells during B. pseudomallei infection, although LPS from B. pseudomallei has been described as less stimulatory (34).…”
Section: Vol 76 2008 B Pseudomallei Infection Costimulates T Cellsmentioning
confidence: 97%
“…We found that LPS could costimulate T cells to make IFN-␥ in the presence of IL-2 to the same on May 10, 2018 by guest http://iai.asm.org/ extent as bacterial infection in both CD4 ϩ and CD8 ϩ T cells. TLR4 expression on memory T cells has been reported (4) and, although stimulation via LPS alone does not result in proliferation nor cytokine production, T cells are able to respond to LPS via TLR4 by upregulating adherence to fibronectin and SOCS3 (39). Thus, LPS may be able to directly costimulate human T cells during B. pseudomallei infection, although LPS from B. pseudomallei has been described as less stimulatory (34).…”
Section: Vol 76 2008 B Pseudomallei Infection Costimulates T Cellsmentioning
confidence: 97%
“…CD4 T cell effector functions (as measured by CD40L and IFN-␥) were not significantly induced or enhanced by MPL in this present study. In some studies, T cell responses to TLR4 agonists have been observed, such as increased adherence and Ca 2ϩ mobilization, but these measures are not necessarily indicators of Ag-independent T cell activation (25,51,52). Therefore, it is likely that the superior adjuvant activity of AS04 resulted from APC-mediated activation of T cells and subsequent B cell activation.…”
Section: How Does As04 Enhance Ab Response Compared With Aluminum Hydmentioning
confidence: 99%
“…In some cases lipopolysaccharide (LPS) (recognized by TLR-4) was reported to stimulate the activation of protein kinase C in CD3 + T cells 53 and perforin production in a subset of CD4 + T cells in patients with ankylosing spondylitis. 54 Moreover, Fukata et al 36 found that LPS-stimulated proliferation of T-effector cells was dependent on Myd88.…”
Section: Toll-like Receptor Engagement Affects Cd4 + T-effector and Tmentioning
confidence: 99%